Assessment of the Role of Primary Care Model in the Management of Non-Communicable Diseases in Busia County - Ogutu, Sylvester Okumu (JOOUST, 2021)
Non-communicable diseases (NCDs) are chronic diseases that cannot be passed from one person to another, like cancer, cardiovascular diseases, chronic respiratory diseases, diabetes, mental and neurological disorders. The emerging rise in NCDs in Kenya has accounted for up to 32% of the total disease-related deaths, and between 2015 and 2018, NCDs accounted for half of the top 20 causes of disease-related deaths in Kenya. Approximately, 50% of all hospital admissions and 55% of hospital deaths in Kenya are attributed to NCDs. Since the Alma-Ata Declaration in 1978, the primary health care model implementation has remained dismal despite government-level commitments. On top of the pervasive economic factors at play, the inability to access affordable and safe primary care services leaves little opportunity for health promotion and preventative medicine that are cornerstones in the fight against NCDs. The goal of the study was to assess the role of primary care model in the management of NCDs. Descriptive facility based cross-sectional study was conducted among 255 patients with confirmed NCDs who received treatment and 41 healthcare providers (key informants) in selected 42 health facilities within Busia County. Data from the patients was collected using semi-structured questionnaires and key informant interview guide was used to collect data from the healthcare providers. Quantitative data was analyzed using SPSS version 23 (a =0.05). Findings revealed a statistically significant association between demographic characteristics and the type of NCD (p < 0.001). Hypertension was found to be the most prevalent NCD, accounting for 51.37% (95% CI=0.45 - 0.57). Majority of the respondents (94.9%) were diagnosed in hospitals, where 86 (33.7%) spent more than 3 hours for their entire visit, and up to 91.4% were not in any NCDs support group in their communities. Only 85 (33.3%) were visited by CHVs in the preceding 6 months, of whom only 61 (71.8%) affirmed that CHVs knew they had NCDs and had discussed NCDs management with them. There was a strong positive correlation between health system factors and PCM (Pearson’s r= 0.765; p < 0.001). This study recommends the County Government of Busia should set aside adequate funds for NCDs in health facilities to ensure the availability and accessibility of necessary health care equipment, drugs and diagnostic equipment, to facilitate proper treatment and management of NCDs in the health facilities. In addition, there is need to intensify campaigns for screening NCDs in the community, and enhance of the role of community health volunteers in NCD management, including the availability of support groups.